2010
DOI: 10.1186/1471-2458-10-142
|View full text |Cite
|
Sign up to set email alerts
|

Geographic access to care is not a determinant of child mortality in a rural Kenyan setting with high health facility density

Abstract: BackgroundPolicy-makers evaluating country progress towards the Millennium Development Goals also examine trends in health inequities. Distance to health facilities is a known determinant of health care utilization and may drive inequalities in health outcomes; we aimed to investigate its effects on childhood mortality.MethodsThe Epidemiological and Demographic Surveillance System in Kilifi District, Kenya, collects data on vital events and migrations in a population of 220,000 people. We used Geographic Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 29 publications
3
58
0
Order By: Relevance
“…This study is consistent with Combier et al (2013), Dummer and Parker (2004), and Moisi et al (2010) that travel time is not associated with neonatal mortality, while studies by Gryzbowski et al (2011), Okwaraji et al (2012, Ravelli et al (2011), andShoeps et al (2011) found a significant association with under-5 mortality and perinatal mortality (stillbirths and neonatal deaths). However, direct comparisons are not warranted for several reasons.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This study is consistent with Combier et al (2013), Dummer and Parker (2004), and Moisi et al (2010) that travel time is not associated with neonatal mortality, while studies by Gryzbowski et al (2011), Okwaraji et al (2012, Ravelli et al (2011), andShoeps et al (2011) found a significant association with under-5 mortality and perinatal mortality (stillbirths and neonatal deaths). However, direct comparisons are not warranted for several reasons.…”
Section: Discussionsupporting
confidence: 78%
“…In such studies, pedestrian travel was the most common form of transport (Combier et al, 2013;Moisi et al, 2010;Okwaraji et al, 2012). The majority of studies consisted of a much larger sample size (Combier et al, 2013;Dummer & Parker, 2004;Grzybowski et al, 2011;Moisi et al, 2010;Okwaraji et al, 2012;Ravelli et al, 2011). Consistent with Combier et al (2013), and Grzybowski et al (2011), we excluded births less than 20 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations